2011
DOI: 10.1111/j.1365-2648.2010.05558.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nurse-facilitated family participation in the psychological care of the critically ill patient

Abstract: Nurse-facilitated family participation in the psychological care may strengthen the lines of defence and resistance against the stressors experienced by the patient during critical illness and improve psychological recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
121
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 48 publications
2
121
0
9
Order By: Relevance
“…No significant statistical differences were found between the groups for incidence of delirium (P=0.176). However, it was observed that investing in the intervention with family members during the critical moment provided long-term benefits to the patient, since the family was able to perform the care maintenance after the acute phase (31) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant statistical differences were found between the groups for incidence of delirium (P=0.176). However, it was observed that investing in the intervention with family members during the critical moment provided long-term benefits to the patient, since the family was able to perform the care maintenance after the acute phase (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Colombo R, Corona A, Praga F, Minari C, Giannotti C, Castelli A, Raimondi F. (24) Prospective observational study 2c 2011 PubMed Black PP, Boore JRP, Parahoo K. (31) Non-randomized clinical trial 2b…”
Section: Pubmedmentioning
confidence: 99%
“…Recent studies (5)(6)(7)(8)(9) have questioned the effectiveness and effects of the implementation of this model of care, and reinforce the importance of producing evidence to support its application in practice. In this sense, it is necessary to use reliable instruments which have been tested and which can measure how health professionals caring for patients and families realize the application of this model in health units.…”
Section: Introductionmentioning
confidence: 99%
“…19 Among non-pharmacological strategies stand out: the psychological care in the ICU, the presence of the patient's family, demobilization of physical restraint, promoting calm, quiet and bright and sound stimuli reduction especially overnight seeking adequate sleep and rest, early mobilization, music therapy, cognitive stimulation, use of early screening scales as the CAM-ICU, adapting the environment to aid in the perception of night and day, use of glasses and hearing aids, early removal of invasive devices and electrolytic disorders correction. 7,5,9,13,18,20,21 The studies analyzed show that research about delirium in the elderly population are still incipient, and that this syndrome is a frequent problem in these patients. The incidence of delirium in the population of 60 years or more in several international studies ranged from 27 to 79%, proving to be a major problem in these patients.…”
mentioning
confidence: 99%
“…2, 5,8,9,13,17,18,19,20,21 Among the pharmacological strategies highlight the use of haloperidol, being recommended for the elderly at half the dose used in adults. 21 The sedative of choice was dexmetomidin.…”
mentioning
confidence: 99%